Reliability of information on varicella history in preschool children (Clinics, 2007)
OBJECTIVE: To verify how reliable is the information provided by parents about the history of varicella in their children. METHODS: 204 parents of previously healthy children attending two municipal day-care centers of São Paulo city were interviewed between August 2003 and September 2005. A standardized form was filled out with information regarding age, sex, history of varicella and other diseases, drug use and antecedent of immunization, After medical history, physical examination and checking of immunization records, 5 ml of blood were collected for ELISA (in house) varicella test. Exclusion criteria were: age less than 1 year or more than 60 months, previous immunization against chickenpox, presence of co-morbidities or recent use of immunosuppressive drugs. Data were filed in a data bank using the Excel 2003 Microsoft Office Program and stored in a PC computer. The exact Fisher test was employed to calculate sensibility, specificity, positive and negative predictive values of history of varicella informed by children's parents. RESULTS: The age of the children varied from 12 to 54 months (median, 26 months; 49 (24%) children had positive history of varicella, 155 (76%) a negative or doubtful history. The predictive positive and negative values of the information were 90% and 93%, respectively (p = 0.0001). CONCLUSIONS: The degree of reliability of information about history of varicella informed by parents of children attending day care centers was high and useful to establish recommendations on varicella blocking immunization in day-care centers.